Figurative language of segregation: the phenomenon of “two schools under one roof” - Mujagić, Mersina; Dupanović, Edin (ExELL, 2025)
Post-war Bosnia and Herzegovina remains a society in which ethno-nationalist rhetoric and war memories permeate public discourse. This paper investigates the use of metaphors in media texts written in English and the Bosnian, Croatian, and Serbian language on the topic of ‘two schools under one roof’. Writing about this peculiar construct within the country’s educational system tackles socio-political factors and their effects on the provision of primary and secondary education. We describe how metaphors as cognitive devices are used to portray educational developments in this post-conflict country and the effects of their use on recipients. The paper points out cases of deliberate metaphor use, which influences recipients’ perspectives on the topic at hand.